2011
DOI: 10.1210/jc.2011-1321
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations of Highly Prevalent Corticosteroid-Binding Globulin Mutations in a Village in Southern Italy

Abstract: A high combined prevalence (3.6%) of these two CBG mutations was detected. The presence of either mutation conferred a propensity to chronic pain. In other communities, individuals with the same genetic background complain more of fatigue than pain, suggesting an environmental effect on the phenotype. These findings, combined with animal CBG gene knockout and human CBG single-nucleotide polymorphism haplotype studies, suggest that CBG influences the endocrine and neurobehavioral response to stress, including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 39 publications
0
13
0
2
Order By: Relevance
“…Our community study in Calabria, Italy (the place of origin of the kindred described earlier [21]) showed a high prevalence of CBG Adelaide and CBG Lyon mutations (3.6%) [78]. CWP, in particular, was found to be common in subjects with the Null or Lyon SERPIN A6 mutation.…”
Section: Genetic Epidemiology Studiesmentioning
confidence: 55%
“…Our community study in Calabria, Italy (the place of origin of the kindred described earlier [21]) showed a high prevalence of CBG Adelaide and CBG Lyon mutations (3.6%) [78]. CWP, in particular, was found to be common in subjects with the Null or Lyon SERPIN A6 mutation.…”
Section: Genetic Epidemiology Studiesmentioning
confidence: 55%
“…We completed a blinded study of an isolated population with an increased frequency of CBG Adelaide and Lyon mutations (3.6%) and found an association between the CBG mutations and chronic pain rather than fatigue, relative to controls, suggesting an environmental effect on the phenotypic expression of CBG mutations (20).…”
Section: Discussionmentioning
confidence: 97%
“…The results showed a high prevalence of CBG null and Lyon mutations (3.6%). Chronic widespread pain, but not chronic fatigue, was found to be common in subjects with CBG mutation 87 .…”
Section: Genetic Epidemiology Studiesmentioning
confidence: 88%